Shariah and legal issues in the Bay' Bithaman-al-Ajil (BBA): a viewpoint - Md. Dahlan, Nuarrual Hilal; Syed Abdul Kader, Sharifah Zubaidah (LexisNexis, 2010)
The primary duty of Islamic banks and financial institutions in Malaysia is to carry out Islamic banking and financial activities and to offer products that are in accordance with Islamic teachings. These products are subject to the scrutiny and approval of the Bank Negara's Shariah Advisory Council ('SAC') and the internal Shariah Advisory Bodies ('SAB') or the Shariah Commitees of the respective financial institutions. Despite having been in existence for more than 25 years, it remains unclear on whether Islamic banks and financial institutions in Malaysia have been satisfactorily carrying out this duty. One area worth examining is the transaction involving house buying, particularly, falling under the purview of the Housing Development (Control and Licensing) Act 1966 (Act 118) and transactions involving houses pending completion. This paper examines this area of transaction and loan agreement, effected via the Bay' Bithaman al-Ajil ('BBA'), that Islamic banking and financial institutions in Malaysia provide. The purpose of this paper is to examine the extent of which the sale and purchase agreement and the loan agreement have complied with the requirements of Islamic law in protecting stakeholders and to provide practical suggestions to improve the existing practice. The functions, roles, establishment and problems plaguing the SAC and the SAB are also examined, particularly in respect of their role in advising the institutions on transactions involving house buying in Malaysia, bearing on provisions of the recent statute - the Central Bank of Malaysia Act 2009 (Act 701), enforced on 19 August 2009. The paper concludes that the current practice of the BBA is contrary to the teachings of Islam and should be modified and revamped until it is fully able to protect the interests of the purchaser/ borrower.